Sensory characteristics of the longissimus thoracis et lumborum and biceps femoris muscles from male and female common eland (Taurotragus oryx) - Needham, Tersia; Laubser, Johannes G; Kotrba, Radim; Bureš, Daniel; Smyth, Heather; Hoffman, Louwrens C (Meat science, 2019)
The sensory attributes of the longissimus thoracis et lumborum (LTL) and biceps femoris (BF) muscles were compared for male (n = 6) and female (n = 6) eland. Descriptive sensory analysis showed that the meat from cows, and the BF muscle, had greater overall flavour scores, primarily characterized as beef-like flavour (r = 0.926). Unfavourable aroma and flavour attributes received low scores, indicating good potential for fresh eland meat to be marketed commercially. The two muscles showed separation from one another regarding both sensory and physical attributes, which should be considered for their commercial sale. Thus, sex had minor influences on the sensory eating quality of eland meat; however, the BF and LTL muscles were considered tough and further ageing thereof should be evaluated.
Keywords: Meat; Odorants; Taste; Male; lidé; Antelopes; Humans; sexuální faktory; odoranty; Game meat; Tenderness; Sex Factors; Animals; Aroma; zvířata; mužské pohlaví; kvalita jídla; Food Quality; antilopy; kosterní svaly; Flavour; Antelope; maso; Muscle, Skeletal; ženské pohlaví; Female; chuť